Slow magnetic relaxation in a Dy3 triangle and a bistriangular Dy6 cluster. Issue 24 (8th June 2022) - Wang, Wen; Shang, Tao; Wang, Juan; Yao, Bin-Ling; Li, Li-Cun; Ma, Yue; Wang, Qing-Lun; Zhang, Yuan-Zhu; Zhang, Yi-Quan; Zhao, Bin
Abstract : Utilizing two different Schiff base ligands, a Dy3 triangular 1 and a Dy3 + Dy3 compound 2 were obtained. The obvious transverse anisotropy and the larger dipole–dipole interactions induce the poor slow magnetic relaxation of 2 . Abstract : Two lanthanide single-molecule magnets (SMMs) [Dy3 (μ3 -OH)(HL-1)3 (H2 O)3 ](NO3 )2 ·3H3 O (1, H3 L-1 = ( E )-3-(((8-hydroxyquinolin-2-yl)methylene)amino)propane-1, 2-diol) and [Dy6 (μ3 -OH)4 (H2 L-2)4 (HL-2)2 (L-2)2 ] (2, H3 L-2 = ( E )-2-hydroxy- N ′-(2-hydroxy-3-methoxybenzylidene)benzohydrazide) were synthesized and characterized structurally and magnetically. Complex 1 contains a triangular Dy3 core in which the three Dy 3+ ions share a μ3 -OH − anion and the deprotonated ligands of (HL-1) 2− serve both capping and bridging functions, while 2 displays a centrosymmetric hexanuclear Dy III structure with two similar Dy3 triangular cores ligated by two fully deprotonated (L-2) 3− ligands, each of which shares two μ3 -OH − anions. All the Dy III ions are eight-coordinated with quasi D 2d or C 2v symmetry. Magnetic studies reveal that 1 exhibited two-step magnetic relaxation under an applied dc field of 800 Oe, with effective energy barriers of 40.1 and 31.0 K for the slow relaxation (SR) and fast relaxation regimes (FR), respectively. Meanwhile, 2 only showed a tail of slow magnetic relaxation at above 2 K. Ab initio calculations have been carried out to show the nature of their different magnetic properties.